Wireless mobile communication and healthcare : 6th International Conference, MobiHealth 2016, Milan, Italy, November 14-16, 2016, Proceedings /: 6th International Conference, MobiHealth 2016, Milan, Italy, November 14-16, 2016, Proceedings. (2017) - Unknown
No abstract available